Evaluasi Program Bantuan Stimulan Perumahan Swadaya (BSPS) pada Kelurahan Tanjung Unggat - Nurbaiti Usman Siam; SUHARDI MUKHLIS; Junidar (STISIPOL Raja Haji, 2021)
The self-help housing stimulant assistance program (BSPS) aims to fulfil citizen’s rights to adequate housing in a healthy, safe, harmonious and orderly environment, to ensure certainty of settling, and to improve low- income communities, those who have limited purchasing power, so they need support from the government to obtain a decent home. In the implementation of the family-based assistance program, of course there is a need for cooperation not only related agencies that must work together but there needs to be a good collaboration with the community as an object of aid activities to help the success of the implementation of the aid program in order to achieve the goals set to the maximum. In this case in particular Tanjung Unggat village, Bukit Bestari sub-district, Tanjungpinang city. The purpose of this study is to find out how the results of the program implementation from the beginning to the end of the program carried out by the village of Tanjung Unggat and to find out the obstacles that occur program in question. The research method used in this study is a descriptive method with a qualitative sampling approach using purposive sampling and using a sampling technique based on sample size, by taking a sample of 17 people consisting of recipients of Tanjung Unggat village assistance, staff of the public housing service staff in the area of cleanliness settlements and Tanjungpinang city park, staff directorate general of housing provison, program implementation assistants, as well as people who are considered to know about implementing BSPS. From the results of the analysis it can be concluded that in the implementation of the BSPS program in Tanjung Unggat village there are still a number of recipients who carry out program activities not in accordance with the programs objectives, but most others have carried out the assistance program in accordance with what has been set namely improving the quality of occupancy to make it more livable than previous.